ASPECTOS PRAGMÁTICOS EN LOS TRABAJOS TEÓRICOS SOBRE TRADUCCIÓN - Hernández Cristóbal, Alicia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Although the terms pragmatics and discourse analysis are not even mentioned in much of the literature of the field, the importance that these theoretical approaches have for translation studies is more and more evident. The number of authors who believe that the translator must be conscious of the discoursive features of the source text is steadily growing. The aim of this paper is to revise how the pragmatic and discoursive aspects are presented in translation studies literature. Special attention will be given to conversational implicatures.